Effect of Methyl-B-Cyclodextrin (MBCD) on In Vitro Capacitation of Buffalo Frozen/Thawed Sperm - Elkhawagah, A.R.; Longobardi, V.; Gasparrini, B.; Sosa, G.A.; Salzano, A.; Aboul-roos, M.E.A.; El-Gaffar, A.E. Abd; Zicarelli, L. (Journal of Buffalo Science, 2014)
The aim of this study was to determine the effect of Methyl-B-Cyclodextrin (MBCD) on capacitation of buffalo sperm. Frozen/thawed semen was incubated in the absence of capacitating agents (negative control), in the presence of 10 µg/ml heparin (positive control) and of 1, 2, 4 and 8 mg/ml MBCD for 2 and 4h. At each incubation time, sperm motility was evaluated by phase contrast microscopy. Capacitation was assessed by the sperm ability to undergo acrosome reaction after lysophosphatidylcholine treatment, evaluated with viability by Trypan blue-Giemsa. After 2 h capacitation increased (P<0.01) in MBCD groups (39.2±1.4, 44.5±3.3, 56.7±1.5 and 62.5±3.8, with 1, 2, 4 and 8 mg/ml MBCD, respectively) compared to the negative and positive controls (27.5±1.0 and 28.0±0.8, respectively). Likewise, after 4 h the percentage of live capacitated sperm was higher at increasing concentration of MBCD (31.0±0.7, 34.5±1.7, 42.0±1.9, 49.2±2.8, 62.3±1.5 and 70.8±1.7 in negative control, positive control and with 1, 2, 4 and 8 mg/ml MBCD, respectively; P<0.01). After 2 h sperm motility was lower (P<0.01) in 4 and 8 mg/ml MBCD groups (43.3±2.1 and 25.0±3.2, respectively) than in negative control, positive control, 1 and 2 mg/ml MBCD groups (55.0±1.8, 48.3±2.8, 61.7±2.8, 56.7±1.1, respectively). After 4 h the lowest sperm motility was observed with higher MBCD concentrations (40.0±0.0, 46.7±4.2, 51.7±4.6, 50.0±0.0, 40.0±3.7 and 6.7±1.1, in negative control, positive control, 1, 2, 4 and 8 mg/ml MBCD, respectively; P<0.01). In conclusion, MBCD improved sperm capacitation in a dose-dependent manner while decreasing the sperm motility at higher concentrations